The impact of coronavirus outbreak on breastfeeding guidelines among Brazilian hospitals and maternity services: a cross-sectional study - Gonçalves-Ferri, Walusa Assad; Pereira-Cellini, Fábia Martins; Coca, Kelly; Aragon, Davi Casale; Nader, Paulo; Lyra, João Cesar [UNESP]; do Vale, Maryneia Silva; Marba, Sérgio; Araujo, Katiaci; Dias, Laura Afonso; de Lima Mota Ferreira, Daniela Marques; Nieto, Gislayne; et al. (Springer Nature, 2021)
Background: The World Health Organization recognizes exclusive breastfeeding a safe source of nutrition available for children in most humanitarian emergencies, as in the current pandemic caused by the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). Despite the Brazilian national guideline protecting breastfeeding practices, there are many concerns about protecting infants from their infected mothers. This study aimed to analyze how the Brazilian hospitals and maternity services promote and support mothers suspected or diagnosed with coronavirus disease (COVID-19). Methods: This is a descriptive cross-sectional and multicenter study which collected data from 24 Brazilian hospitals and maternity services between March and July 2020. Representatives of the institutions completed a questionnaire based on acts to promote and support breastfeeding, the Baby-Friendly Hospital Initiative, and Brazil’s federal law recommendations. Results: The results showed that in delivery rooms, 98.5% of the services prohibited immediate and uninterrupted skin-to-skin contact between mothers and their infants and did not support mothers to initiate breastfeeding in the first hour. On the postnatal ward, 98.5% of the services allowed breastfeeding while implementing respiratory hygiene practices to prevent transmission of COVID-19. Companions for mothers were forbidden in 83.3% of the hospitals. Hospital discharge was mostly between 24 and 28 h (79.1%); discharge guidelines were not individualized. Additionally, a lack of support was noticed from the home environment’s health community network (83.3%). Hospital and home breast pumping were allowed (87.5%), but breast milk donation was not accepted (95.8%). There was a lack of guidance regarding the use of infant comforting strategies. Guidelines specific for vulnerable populations were not covered in the material evaluated. Conclusions: In Brazil, hospitals have not followed recommendations to protect, promote, and support breastfeeding during the COVID-19 outbreak. The disagreement between international guidelines has been a major issue. The absence of recommendations on breastfeeding support during the pandemic led to difficulties in developing standards among hospitals in different regions of Brazil and other countries worldwide. The scientific community needs to discuss how to improve maternal and infant care services to protect breastfeeding in the current pandemic.
Keywords: Brazil; Breastfeeding; Breastfeeding guidelines; Breastfeeding practices; COVID-19; Milk bank; Public health; Skin-to-skin